Addressing Bias in Non‐Probability Fisheries Surveys Using Multilevel Regression and Poststratification Approaches - Zachary Radford; Wendy Edwards; Samantha Hook; Bridgid Bell; Rebecca Mills; Grace Farrell; Martin J. Genner; Stephen D. Simpson; Kieran Hyder (Fish and Fisheries, 2026)
Quantifying harvest of fish stocks is challenging as census data are often unavailable, so surveys are required. Traditional probability‐based surveys use random sampling to obtain representative data that can be scaled to estimate total impact. However, these surveys are costly, so cheaper, non‐probability, citizen science surveys of self‐selected participants are becoming commonplace. Respondents in these surveys may not be representative and inclusion probabilities are unknown, making weighting difficult. This resembles exit polls, which successfully predict election outcomes using Multi‐level Regression and Post‐stratification (MRP), but this has not been tested in fisheries. This study applied MRP to quantify UK recreational sea angling (RSA) participation and catches using data from the UK Sea Angling Diary Project. This represents a ‘worst‐case’ scenario, as there is no sampling frame and no mandatory reporting. Five Bayesian multi‐level models were fitted to two survey datasets: one quantifying participation and days fished, and another location, numbers, and weight of fish caught. Predictions were post‐stratified using UK census data. Estimates from the traditional reweighting and MRP were compared, and a simulation approach was used to assess the accuracy and precision of the two methods. MRP reduced self‐selection bias and improved estimates in under‐represented groups, producing a 40% and 61% improvement for participation and catch, respectively. Average annual UK RSA participation was estimated to be 688,000 anglers, with 6.1 million days fished. Annual catch estimates were 32.4 million fish, weighing 14,876 t. This study demonstrates the value of MRP for reducing bias when analysing and scaling non‐probabilistically collected survey data.

Determinants of antimicrobial resistance in biosolids: A systematic review, database, and meta-analysis - Joanna Ciol Harrison; Grace V. Morgan; Aditya Kuppravalli; Nicole Novak; Michael Farrell; Sienna Bircher; Emily Garner; Nicholas J. Ashbolt; Amy Pruden; Rebecca L. Muenich; Treavor H. Boyer; Clinton Williams; et al. (Science of The Total Environment, 2024)

Population pharmacokinetics and exposure–response relationships of maribavir in transplant recipients with cytomegalovirus infection - Ivy H. Song; Grace Chen; Siobhan Hayes; Colm Farrell; Claudia Jomphe; Nathalie H. Gosselin; Kefeng Sun (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Maribavir is approved for management of post-transplant cytomegalovirus (CMV) infections refractory and/or resistant to CMV therapies at a dose of 400 mg twice daily (BID). Population pharmacokinetic (PopPK) and exposure–response analyses were conducted to support the appropriateness of 400 mg BID dosing. A PopPK model was developed using non-linear mixed-effects modeling with pooled maribavir plasma concentration–time data from phase 1 and 2 studies (from 100 mg up to 1200 mg as single or repeated doses) and the phase 3 SOLSTICE study (400 mg BID). Exposure–response analyses were performed for efficacy, safety, and viral resistance based on data collected in the SOLSTICE study. Maribavir PK after oral administration was adequately described by a two-compartment model with first-order elimination, first-order absorption, and an absorption lag-time. There was no evidence that maribavir PK was affected by age, sex, race, diarrhea, vomiting, disease characteristics, or concomitant use of histamine H 2 blockers, or proton pump inhibitors. In the SOLSTICE study, higher maribavir exposure was not associated with increased probability of achieving CMV DNA viremia clearance, nor with reduced probability of treatment-emergent maribavir-resistant CMV mutations. A statistically significant association with maribavir exposure was identified for taste disturbance, fatigue, and treatment-emergent serious adverse events, while transplant type, enrollment region, CMV DNA level at baseline, and/or CMV resistance at baseline were identified as additional risk factors for these safety outcomes. In conclusion, the findings of these PopPK and exposure–response analyses provide further support for the recommended maribavir dose of 400 mg BID.